Qualimeyric Approach to Diagnosing the Competences of University Graduates - O. F. Shikhova; Y. A. Shikhov (Russian State Vocational Pedagogical University, 2015)
The paper considers the implementation of the qualimetric approach, particularly - the group expert estimation method, for specifying the graduates' actual competences in compliance with the federal state educational standards; allocation of groups and subgroups of the given competences; and pedagogic expertise of the competence oriented estimation means. The authors maintain that the above method is the most perspective, objective and standardized one among the existing diagnostic methods. The pedagogic expertise is carried out according to the prescribed algorithms by a group of previously selected experts, their competences, coordination and number guaranteeing the admissible error margin and value relevance level. The algorithm of complex attestation tasks development is designed for diagnosing the bachelors' readiness for professional activity in technological profile.